China Lake : a journey into the contradicted heart of a global climate catastrophe - Baumgart, Barret, 1987- (University Of Iowa Press, 2017)
"Barret Baumgart's literary debut presents a haunting and deeply personal portrait of civilization poised at the precipice, a picture of humanity caught between its deepest past and darkest future. In the fall of 2013, during the height of California's historic drought, Baumgart toured the remote military base, NAWS China Lake, near Death Valley, California. His mother, the survivor of a recent stroke, decided to come along for the ride. She hoped the alleged healing power of the base's ancient Native American hot springs might cure her crippling headaches. Baumgart sought to debunk claims that the military was spraying the atmosphere with toxic chemicals to control the weather. What follows is a discovery that threatens to sever not only the bonds between mother and son but between planet Earth and life itself. Stalking the fringes of Internet conspiracy, speculative science, and contemporary archaeology, Baumgart weaves memoir, military history, and investigative journalism in a dizzying journey that carries him from the cornfields of Iowa to drought-riddled California, from the Vietnam jungle to the caves of prehistoric Europe and eventually the walls of the US Capitol, the sparkling white hallways of the Pentagon, and straight into the contradicted heart of a worldwide climate emergency"--